Postgraduate Students’ Challenges in Developing Social Solidarity in the Multicultural Community of an Islamic University - Hussien, Suhailah binti; Mohd Noor, Nor Athiah binti (Literasi: Jurnal Ilmu Pendidikan, 2025)
International Islamic University (IIUM) is an institution of higher education that is grounded in Islamic principles, distinguishing its unique characteristics in its curriculum, student development and academic professionalism. As one of the public Islamic universities in Malaysia, the International Islamic University (IIUM) aims to establish itself as a hub of academic distinction with a strong focus on promoting Islamic values and global engagement. The vision and mission of the university reflect a commitment to the integration of knowledge, practices and the diversity of its staff and student population. Currently, the university consists of undergraduate and postgraduate students from 56 countries. As a result, fostering social unity and solidarity to realise its mission of Ummatic development presents a significant challenge.  In view of this, the study aims to investigate the experiences of students in IIUM, focusing on the challenges of postgraduate students in developing social solidarity within the diverse Muslim community during their academic journey. The study employed the phenomenological research design, where ten participants were selected using purposive sampling. The data were then analyzed using thematic analysis. Research findings of the study showed that participants experienced challenges in developing social solidarity which revealed two major themes, collective commitment and student body and program. It emphasizes the need to improve the curriculum, co-curriculum, and learning environment that considers the multicultural background of the students. The study highlights the necessity for collaboration between educators and university administrators in enhancing curriculum, pedagogy, and administrative procedures that foster social solidarity among multicultural student populations in higher educational institutions